Contextual and Project-Based Learning in IPAS Instruction within the Merdeka Curriculum: A Case Study at MI Al-Azhar Muara Pinang - Ariswari, Nikma; Zulysa, Deka; Dhori, Muhammad (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2025)
This study explores the implementation of the Merdeka Curriculum in the teaching of IPAS (Integrated Natural and Social Sciences) for fifth-grade students at MI Al-Azhar Muara Pinang. Employing a qualitative case study approach, data were gathered through participatory observation, semi-structured interviews, documentation, and literature review over a four-week period. Thirty students and one class teacher participated in the study. Findings reveal that the integration of project-based activities, such as the photosynthesis experiment, successfully fostered students’ scientific curiosity, collaborative skills, and conceptual understanding. These activities aligned with constructivist and experiential learning principles, allowing students to internalize knowledge through direct engagement. Nevertheless, challenges remain, particularly regarding teacher reliance on conventional lecture-based methods and limited media design skills. To address these issues, the study recommends leveraging digital resources, such as educational videos, to enhance learning engagement and support teachers in delivering interactive content. The study highlights the practical benefits of the Merdeka Curriculum in reducing teacher workload and enhancing student motivation, while also emphasizing the need for continuous professional development to optimize curriculum implementation. Limitations include the study's restricted geographic scope and reliance on qualitative data. Future research should consider comparative studies across multiple schools and incorporate mixed methods to deepen the analysis of learning outcomes.